THE INFLUENCE OF SOCIAL MEDIA CONTENT, INFLUENCER MARKETING, AND WORD OF MOUTH ON HEALTHCARE SERVICE USER DECISIONS AT PT SPRING ISLAND TRAVEL MEDAN - Debby Junita Inggriani Panjaitan; Gavrilsca; Enda Gunanta Surbakti; Holfian Daulat Tambun Saribu; Rintan Saragih (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to examine the effect of social media content, influencer marketing, and word of mouth on the decision-making of healthcare service users at PT Spring Island Travel Medan. The background of this research is based on the increasing role of digital media in shaping perceptions and decisions of prospective medical travelers, particularly in selecting healthcare services in Malaysia. This study employs a quantitative approach using descriptive and explanatory methods. The sample consists of 96 respondents, selected using accidental sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that social media content has a positive and significant effect on users’ decision-making. Meanwhile, influencer marketing does not have a significant partial effect. On the other hand, word of mouth has a positive and significant influence and is identified as the most dominant variable affecting users’ decisions. Simultaneously, all three independent variables have a significant effect on healthcare service decisions at PT Spring Island Travel Medan. These findings indicate that trust derived from other people’s experiences remains the primary factor in making medical travel decisions, although digital content still plays an important supporting role in influencing user decisions.